Seed desiccation tolerance and dormancy of three endangered New Zealand species: Carmichaelia williamsii, Clianthus puniceus and Hibiscus diversifolius - Park, M.J.; Mcgill, C.R.; Williams, W.M.; Mackay, B.R. (NZGA: Research and Practice Series, 2010)
At least one third of New Zealand's indigenous plant species are threatened with extinction and strategies for conserving endangered flora are urgently required. One strategy is to use ex situ seed storage as a complement to in situ conservation. Successful ex situ storage of seed requires knowledge of the seed storage behaviour, optimal storage conditions and germination requirements of the species being stored. For many threatened species, however, this information is either incomplete or unavailable. In this study, preliminary experiments were conducted with three threatened species, Carmichaelia williamsii, Clianthus puniceus and Hibiscus diversifolius, to determine their desiccation tolerance and dormancy status. Seeds were tested for germination following desiccation and dormancy-breaking treatment. Seeds of all three species could be dried to moisture contents of 2.9-3.7% without losing viability. All three species became predominantly hardseeded at approximately 10% moisture content. However, C. puniceus became permeable to water again at moisture contents below 6%. In all species, manual scarification of seeds improved germination to 96-100% compared with 5-20% in untreated seeds. Dormancy in these species is a function of the seed coat preventing water uptake by the dry seed. While seeds of these species are most likely desiccation tolerant and thus can potentially be stored for long periods under conventional conditions, the loss of dormancy of C. puniceus at very low moisture contents is of concern. More work is needed to confirm the long-term storage behaviour of these species. Keywords: ex situ conservation, seed storage behaviour, New Zealand flora